Analysis of the impact of the level of knowledge on the decision to vaccinate - Makara-Studzińska, Marta; Kalinowski, Paweł; Podstawka, Danuta; Śliwińska, Zofia; Śliwiński, Zbigniew (Medical Studies/Studia Medyczne, 2015)
Introduction : Infectious diseases are still a significant medical and social problem in the contemporary world. The most effective and at the same time the least expensive way to become protected against infectious diseases is vaccinations. Appropriate education of the society referring to the prevention of infectious diseases such as measles, diphtheria, or pertussis can contribute to changing the attitudes of many parents to mandatory and recommended vaccinations. Aim of the research: The analysis of the impact of the level of knowledge on making decisions about administering preventive vaccinations. Material and methods : The study included 370 participants (308 women and 62 men). They were students of Lublin universities and young parents living in the Lublin voivodeship. The research tool was an author-made questionnaire consisting of 20 closed questions. For the statistical analysis of research results the methods of descriptive statistics, the χc2 test, and Cramer’s V correlation coefficient were used. Results : As many as 98% of the respondents exhibiting a higher level of knowledge declared future regular vaccinations of their children in accordance with the official recommendations. Among people with a low level of knowledge, only 45% declared such regularity in their children’s vaccination. As many as 62% of the respondents who lacked knowledge on vaccinations failed to have voluntary vaccinations administered. In comparison, among those with high level of knowledge, 50% never had recommended vaccinations administered. Conclusions : The level of knowledge has a significant impact on the decisions on administering preventive vaccinations in the studied population. Respondents who had a higher level of knowledge more frequently declared administering vaccinations regularly, both to themselves and their children.